Hydrodynamic Techniques in Well Control: In Professional Point of View (American Journal of Energy and Natural Resources, 2023)
The purpose of hydrodynamic methods is to understand the motion of fluids. The field of hydrodynamics has expanded widely in the petroleum industries and takes into account the energy of a fluid - the effect of pressures - the continuous matter, in short. Hydrodynamic theory deals with solving problems in oil and gas fields. Well control techniques focus on not losing control of the well in the first place. Because it is one of the most important aspects of drilling operations. Kicks can lead to explosions with potential loss of life and equipment. Choosing the right way to kill the well is very important and protects against human and equipment losses. Therefore, this study will choose the appropriate method for killing the well based on which conditions and characteristics of the well from a professional and safe point of view. In this study I used Kill sheet Excel model to compare the killing methods in terms of speed, efficiency, ambient environment, and well characteristics. Findings showed that the concurrent method is the best way to kill thr well if all resources and equipment are available at the drilling site, After that comes the engineer’s method if the calculations were done correctly. Because it saves time with only one cycle and reduces casing pressure. Finally, the Driller method because it consumes more time and more circulation which leads to an increase in casing pressure. Thus, it can be said that this study enables us to choose the appropriate method for killing the well from a heuristic point of view.